2000
DOI: 10.1021/jp001947q
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Rate Coefficients for the Reactions of Br(2P3/2), Cl(2P3/2), and O(3PJ) with BrONO2

Abstract: A laser flash photolysis-resonance fluorescence technique has been employed to investigate the kinetics of reactions of the important stratospheric species bromine nitrate (BrONO 2 ) with ground-state atomic bromine (k 1 ), chlorine (k 2 ), and oxygen (k 3 ) as a function of temperature (224-352 K) and pressure (16-250 Torr of N 2 ). The rate coefficients for all three reactions are found to be independent of pressure and to increase with decreasing temperature. The following Arrhenius expressions adequately d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 42 publications
4
40
0
Order By: Relevance
“…Inorganic bromine species interact through 30 gasphase and heterogeneous photochemical reactions. Simulations include the reaction of BrONO 2 +O( 3 P)→BrO+NO 3 , since several studies (Soller et al, 2001;Sinnhuber et al, 2002) found that this reaction can lead to increasing daytime BrO amount above 25 km, especially at low latitudes. Updated kinetic and photochemical data for bromine species are taken from the JPL compilation evaluation 15 (Sander et al, 2006).…”
Section: Bromine Speciesmentioning
confidence: 99%
“…Inorganic bromine species interact through 30 gasphase and heterogeneous photochemical reactions. Simulations include the reaction of BrONO 2 +O( 3 P)→BrO+NO 3 , since several studies (Soller et al, 2001;Sinnhuber et al, 2002) found that this reaction can lead to increasing daytime BrO amount above 25 km, especially at low latitudes. Updated kinetic and photochemical data for bromine species are taken from the JPL compilation evaluation 15 (Sander et al, 2006).…”
Section: Bromine Speciesmentioning
confidence: 99%
“…O + BrONO 2 . The recommendation is based on the study of Soller et al [1221] that employed the laser flash photolysis -res onance fluorescence technique and covered the temperature range 227 -339 K. The recommended uncertainty parameters are larger than those reported by Soller et al pending independent confirmation of their results. Burkholder [198] has coupled laser flash [159] were not considered.…”
Section: -81mentioning
confidence: 99%
“…The model results were sampled at the same location and time as the MLS individual profiles. Reaction rates were taken from the JPL 2002 recommendations (Sander et al, 2003) with the added reaction (Soller et al, 2001)…”
Section: Comparisons With Numerical Modelsmentioning
confidence: 99%
“…where BrO obs and BrO mod are the BrO volume mixing ratio of the observations and the photochemical model at a given local time t, and at a particular pressure level p; where NO MLS y is the NO y volume mixing ratio derived from the N 2 O MLS measurements using the relationships described by Sugita et al (1998) and NO mod y is the volume mixing ratio used in the photochemical model. In Eq.…”
Section: Diurnal Variationmentioning
confidence: 99%